1984
DOI: 10.1002/1520-6629(198410)12:4<312::aid-jcop2290120404>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Daily event causation: An approach to elderly life quality

Abstract: A conceptual framework for analyzing the role of daily events in the quality of life (QOL) of the elderly is presented. Concepts involving perceptions of control over the causation of daily events are shown to relate to positive and negative aspects of adjustment. Prior research by the authors has shown the utility of assessing the following event sequence: causation of event, response to event, outcome of event activity. The elements in this sequence can be related independently to QOL, and each or all can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

1987
1987
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
6
0
2
Order By: Relevance
“…This two-factor model of well-being (Reich & Zautra, 1981;Zautra & Reich, 1983) encouraged us to attend to the measurement of positive and negative events (Zautra, Guarnaccia, & Dohrenwend, 1986;Zautra, Guarnaccia, Reich, & Dohrenwend, 1988) to further test this model. Along the way, we examined the influence of cognitive and personality features on affective ratings and perceptions of personal control over events (Reich & Zautra, 1984;Wright, Zautra, & Braver, 1985).…”
Section: Why Study Positive Events?mentioning
confidence: 99%
“…This two-factor model of well-being (Reich & Zautra, 1981;Zautra & Reich, 1983) encouraged us to attend to the measurement of positive and negative events (Zautra, Guarnaccia, & Dohrenwend, 1986;Zautra, Guarnaccia, Reich, & Dohrenwend, 1988) to further test this model. Along the way, we examined the influence of cognitive and personality features on affective ratings and perceptions of personal control over events (Reich & Zautra, 1984;Wright, Zautra, & Braver, 1985).…”
Section: Why Study Positive Events?mentioning
confidence: 99%
“…Focusing on positive daily events, high mastery may result in stronger increases in well-being because positive events are often sought after and perceived as under one’s own control [ 19 ]. The person is an active agent rather than a passive recipient in the production of positive events [ 51 52 ] and this is amplified in the context of childhood trauma.…”
Section: Introductionmentioning
confidence: 99%
“…It should not be considered a unidimensional, bipolar positivenegative condition (Bradburn, 1969;Diener & Emmons, 1985;Herzberg, 1966;Lawton, 1983a;Reich & Zautra, 1981Zautra & Simons, 1979). With two affect systems operating, the differential impact of the two types of event transactions (demands and desires) on those systems might be expected and has been found in research on groups of young-and middle-aged adults (Reich & Zautra, 1984;Zautra & Reich, 1980;Zeiss, Lewinsohn, & Munoz, 1979). In general, these investigators found that experiencing desired events increases positive aspects of well-being but has little effect on reducing negative affect; conversely, demand transactions are associated with negative affect but only inconsistently with positive aspects of wellbeing.…”
mentioning
confidence: 99%